Effect of sintering parameters on mechanical properties of injection moulded Ti-6Al-4V alloys - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2009)
This paper describes the microstructural and mechanical properties of injection moulded Ti-6Al-4V parts. Ti-6Al-4V powder was injection moulded with wax based binder. The critical powder loading for injection moulding was 67.5 vol.-% for feedstock. Binder debinding was performed with solvent and thermal method. After debinding the samples were sintered at different temperatures and times in vacuum atmosphere (10(-4) torr). Metallographic studies were conducted to determine to extend densification and the corresponding microstructural changes. The results show that Ti-6Al-4V powder could be sintered to a maximum 99% of theoretical density. Maximum ultimate tensile strength and hardness were obtained 704 MPa and 38.6 HRC at 1275 degrees C for 10 h.
Keywords: Powder injection moulding; Ti-6Al-4V alloy; Sintering; Mechanical properties; POWDER